The internal propeptide of the ricin precursor carries a sequence-specific determinant for vacuolar sorting - Frigerio, Lorenzo; Jolliffe, Nicholas A; Di Cola, Alessandra; Hernández Felipe, Doramys; Paris, Nadine; Neuhaus, Jean-Marc; Lord, J Michael; Ceriotti, Aldo; Roberts, Lynne M (My University, 2001)
Ricin is a heterodimeric toxin that accumulates in the storage vacuoles of castor bean (Ricinus communis) endosperm. Proricin is synthesized as a single polypeptide precursor comprising the catalytic A chain and the Gal-binding B chain joined by a 12-amino acid linker propeptide. Upon arrival in the vacuole, the linker is removed. Here, we replicate these events in transfected tobacco (Nicotiana tabacum) leaf protoplasts. We show that the internal linker propeptide is responsible for vacuolar sorting and is sufficient to redirect the ricin heterodimer to the vacuole when fused to the A or the B chain. This internal peptide can also target two different secretory protein reporters to the vacuole. Moreover, mutation of the isoleucine residue within an NPIR-like motif of the propeptide affects vacuolar sorting in proricin and in the reconstituted A-B heterodimer. This is the first reported example of a sequence-specific vacuolar sorting signal located within an internal propeptide.
Keywords: C-TERMINAL PROPEPTIDE; ARABIDOPSIS-THALIANA; COMMUNIS AGGLUTININ; TARGETING RECEPTOR; STORAGE PROTEINS; TRANSPORT; EXPRESSION; ACCUMULATION; PROTOPLASTS; PHASEOLIN